A Kinetic Model Describing the Interaction of Bovine Prothrombin Fragment 1 with Calcium Ions - Kabis, Charles W; Sarasua, Martha M; Gottschalk, Karen E; Bourne, Carolyn D; Pedersen, Lee G; Jackson, Craig M; Hiskey, Richard G; Koehler, Karl A (Thrombosis and Haemostasis, 1985)
A kinetic model is derived for the interaction of bovine prothrombin fragment 1 with calcium ions. The model requires binding of a minimum of two calcium ions for induction of the observed biphasic fluorescence decrease as a function of time. The model is shown to be consistent with experimental kinetic and equilibrium data by fitting theoretical curves for the biphasic fluorescence change to the data through exact solution of the nonlinear differential rate equations derived from the model. The rate constants for the binding of these two required calcium ions are calculated from the solutions as best fit parameters. The thermodynamic equilibrium constants, K1 and K2, for the binding of these two calcium ions are calculated from ratios of the forward and reverse rate constants as 0.6 × 104 and 5.4 × 104, respectively. Thus, the model correctly predicts positively cooperative calcium ion binding for at least the two calcium ions required to induce fluorescence quenching.
Keywords: Prothrombin; Fluorescence; Calcium; Kinetics